Research of power line communication based on independent component analysis - GAO Qiang; HUANG Li-yan; HOU Si-zu; ZHAO Zhen-bing (Tongxin xuebao)
According to channel characteristics of power line communication（PLC）,a scheme of applying independent component analysis to PLC system was proposed.The system model was constructed by the transmission characteristic of power line.The experiment and simulation show that the weak signals can be extracted and decoded from the trans-mission signals accurately,so that the distance of transmission can be improved.The model requires less restriction con-ditions which makes the model versatile in engineering.